The effects of secretome of umbilical cord mesenchymal stem cells on regeneration of sciatic nerve defects in Sprague dawley rats. - Aryadi Kurniawan; Ismail Hadisoebroto Dilogo; Jeanne Adiwinata Pawitan; Wahyu Widodo; Ihsan Oesman; Ade Martinus (PLoS ONE)
Background and purpose Current treatments for peripheral nerve defects are suboptimal. Mesenchymal stem cell (MSC) implantation holds promise, with studies indicating their efficacy through the secretome. This study aims to assess the secretome's potency in regenerating peripheral nerve defects. Animals and methods Twenty-eight spraque dawley (SD) rats were divided into four groups, with a 10mm segmental sciatic nerve defect created. Group I received autografts, while Groups II, III, and IV had proximal and distal nerve stumps fixed with a conduit. Group II received MSC implantation, Group III received umbilical cord MSC secretome, and Group IV was treated with silicone conduits. Motoric recovery was assessed using the Sciatic Functional Index (SFI) at 6, 9, and 12 weeks. After 12 weeks, rats were sacrificed for measurements of gastrocnemius muscle weight ratio and sciatic nerve histomorphometry. Result The highest ratio of the gastrocnemius muscle were found in groups 1 and 3, namely 0.7 ± 0.06 and 0.7 ± 0.2 (p <0.001). The highest number of myelinated axons was found in group 1 and 3, namely 175.1 ± 15.9 and 168.9 ± 11.7 (p <0.001). The secretome had the similar effectiveness with autograft in promoting regeneration of the sciatic nerve defect. Interpretation The secretome of the umbilical cord MSC can be a novel therapy in replacing autografts for the management of peripheral nerve defects.